Vaginal isolation of beta-haemolytic Streptococcus from bitches with and without neonatal deaths in the litters - Guerrero López, Ana Elizabeth (2018)
The aim of the study was to identify beta-haemolytic streptococci in the vagina of bitches who had delivered healthy litters and bitches who had delivered litters in which neonatal deaths occurred. Fifty-one bitches divided into two groups were used. Group 1 (G1) included 28 bitches that had delivered healthy litters and group 2 (G2) included 23 bitches that had delivered puppies who died in the neonatal period. Two vaginal samples were taken, one in proestrus and the other at the end of gestation (EG). Beta-haemolytic Streptococcus (BS) was isolated from 16 bitches (57%) in G1 and from 21 bitches (91%) in G2. The bacteriological cultures, serological tests (Streptex®) and PCR assay allowed identification of Streptococcus canis and Streptococcus dysgalactiae in G1 and G2. Ultramicroscopic studies allowed the observation of M Protein and capsules in strains of S. dysgalactiae and S. canis in G1 and G2. The S. canis strains isolated from G2 showed thicker capsules than S. canis strains isolated from G1 (234 ± 24.2 vs 151.23 ± 28.93 nm; p < .001.). No differences were observed in capsule thickness between strains of S. dysgalactiae isolated from G1 and G2 (210 ± 13.54 vs 211.66 ± 19.67 nm; p > .70). All strains of beta-haemolytic Streptococcus isolated were penicillin sensitive. Penicillin was administered from EG to 5 days post-partum in 10 G2 females with isolation of BS (G2A). Saline solution was administered in eleven G2 females with isolation of BS (G2B). Ninety per cent of the puppies survived in G2A and 25% survived in G2B. Our results suggest BS is involved in canine neonatal deaths.